Experimental Models of B Cell Tolerance in Transplantation - Cowan, Michelle L. (2011)
Immunologic tolerance is the ultimate goal of organ transplantation yet, is rarely attainable and an infrequent event in humans. Even with the use of conventional immunosuppression, which has successfully improved short-term allograft survival, long-term allograft survival has remained static and is complicated by serious side effects secondary to the long-term use of immunosuppressive agents. Accordingly, over the past several decades, there has been a push to fully understand both the cellular and molecular mechanisms that play a role in the induction and maintenance of tolerance, with recent data implicating B cells and donor specific alloantibody as a barrier to and potential mediator of allograft tolerance. The study of B cells and alloantibody in transplant tolerance has evolved over recent years from using rodent models to large animals to non-human primate models. This review will discuss the role of B cells and alloantibody as antagonists and facilitators of transplantation tolerance, and highlight the experimental models developed for elucidating the mechanisms of B cell tolerance to alloantigen.